Experiencias in situ sobre métodos de evaluación en la institución educativa Liceo VAL (2023)
This project aims to show the different evaluative ways that exist in the educational field. All the while, in these spaces there may be people who may find learning difficult through conventional education methods. In this sense, the research question addressed in this presentation was how the curriculum can help to improve the ways in which people with disabilities learn. To answer this question, a pilot project was carried out at the Vida Amor Luz high school in the Barrios Unidos ́s town in the eighth and ninth grades. Using a qualitative method through interviews with teachers about the curriculum and their adaptation to students with special educational necessities, it was established that curricular innovation strengthens equity in the classroom. In general, the results indicate that to have satisfactory teaching processes, the student population and all its academic and social needs must be taken into account, including those associated with disability.